Shrub‐rings used to reconstruct drought history of the central Alxa desert, northwest China. (31st March 2021) - Ding, Ai‐Jun; Xiao, Sheng‐Chun; Peng, Xiao‐Mei; Tian, Quan‐Yan; Han, Chao
Abstract: The climate history of the Alxa desert of northwestern China must be sought both in recent instrumental records (dating from 1960) and in high‐resolution proxy data. Climate proxies are scarce in desert areas; however, long‐lived desert shrubs can offer one such proxy. We have used shrub‐ring data from Zygophyllum xanthoxylum, collected in the central Alxa desert, to reconstruct the Self‐calibrating Palmer Drought Severity Index (scPDSI) for the period 1880–2015. The data covers the May–July growth season. When we compared the history constructed from the shrub‐ring data with the instrumental data collected 1960–2015, we found that the reconstructed history explained 41% of the variance in scPDSI data (40% after adjusting for loss of degrees of freedom). The reconstructed history shows that this region has experienced six persistent droughts and four seasons wetter than usual during the period under study. Of note is a severe drought event in 1920s that affected much of northern China (as noted in contemporary documents). The droughts and wet seasons identified in our reconstruction are consistent with reports from other researchers who have studied the climate history or the region. Our study suggests that it is feasible to reconstruct climate history using shrub‐ring data from long‐lived desert shrubs. Abstract : Radial growth of long‐lived desert shrubs, Zygophyllum xanthoxylum was mainly affected by the pre‐growing‐season and growing‐season precipitation. It provides opportunity to reconstruct the climate history in the desert hinterland. The first attempt to reconstruct a regional history of scPDSI using Z. xanthoxylum shrub‐ring‐width records. The reconstruction spans the years 1880–2015.